ANALYSING BUSINESS ZAKAH PAYMENT TOWARDS KUALA LUMPUR COMPANIES BY THE APPLICATIONS OF MICROSOFT EXCEL - Rikinorhakis Ridwan; Siti Maziah binti Ab Rahman; Putra Faizurrahman Zahid (International Journal of Accounting, Finance and Business, 2024)
One of the five pillars of the Islamic faith is zakah, an obligatory form of "charity" that all Muslims are required to pay. Zakah is used to cleanse property, but it is also used to cleanse the hearts of those who pay it of greed and selfishness. Corporate zakah from Muslim businesses is still relatively low, even though annual zakah collections are steadily rising. It is due, in part, to uncertainties regarding the way the Zakah institution is handling the money. The purpose of this study was to ascertain the businesses' business zakah payments to the zakah institution. this study tries to apply the Commitment Trust Theory (TKK) (Morgan & Hunt, 1994). The material benefits and perception are the factors that the researcher looks in the fill gaps when looking at that theory. The perception of zakah Institutions (ZI) and material benefits are the antecedents that impact business zakah payments. To test the hypothesis, 31 questionnaires in total were examined. Data were gathered for this study using questionnaires, a quantitative method of data collection. The study's focus is on Kuala Lumpur, Malaysian businesses that are eligible to pay business zakah. The data was run by Microsoft Excel 2016. According to data from this study, the materials benefits had a favorable impact on business responsibility and encouraged business companies' zakah payment. Additionally, the perceptions of zakah institutions have an impact on how business zakah payers behave in terms of compliance.